2018
DOI: 10.1002/jssc.201800605
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discovery and global characterization of multiple components in corn silk using a multivariate data processing approach based on UHPLC coupled with electrospray ionization/quadrupole time‐of‐flight mass spectrometry

Abstract: Corn silk is an important traditional Chinese medicine which has been widely used as diuretic, antilithiasic, uricosuric, antiseptic, etc. for thousands of years. However, it is a pity that the chemical ingredients in corn silk, especially the constituents absorbed into blood, are unclear up to now. The aim of our study was to investigate the multiple components of corn silk in vitro and in vivo. In this present study, a sensitive and rapid method using ultra high performance liquid chromatography coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Information on herbal compounds can be obtained in two ways. One method is directly based on compound analysis techniques [7][8][9], and the other is based on the retrieval from database and literature [1,10,11]. Herbal medicines contain multiple compounds with different polarities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on herbal compounds can be obtained in two ways. One method is directly based on compound analysis techniques [7][8][9], and the other is based on the retrieval from database and literature [1,10,11]. Herbal medicines contain multiple compounds with different polarities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the herbal compounds in each extract may not be exactly the same as those in databases and literature. Compared with the second method, the results of compound analysis techniques (e.g., LC-MS/MS) may better reflect the true composition of herbal extracts [8,9]. Recently, with the development and use of metabolome data repositories (e.g., METLIN, Human Metabolome Database, and MassBank) and associated data analysis tools (e.g., Progenesis QI software, CAMERA, and SF-Matching) [12,13], the LC-MS/MS technology has been widely employed in the study of chemical compounds of herbal medicines, which is a feasible analytical method for the rapid discovery and global characterization of multiple compounds in herbal medicines [7-9, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, UHPLC‐Q‐TOF‐MS/MS has been widely employed in the study of chemical components and pharmacological actions of TCM, especially for the understanding of bioactive constituents and the related research on mechanisms of action of TCM worldwide. Currently, with the perfect integration of UHPLC‐Q‐TOF‐MS/MS and serum pharmacochemistry methods, the active ingredients migrating into blood from some Chinese herbs have been successfully illuminated, including the alcohol extract of corn silk , the leaves and fruits of Acanthopanax senticosus Harms , Radix Polygalae , prescription AS1350 , and others .…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are mainly two ways to obtain the information of herbal compounds. One method is directly based on the compound analysis techniques (Li et al, 2020;Liu et al, 2018a;Wang et al, 2019); the other method is based on the retrieval from the database and literature (Ding et al, 2020;Li et al, 2017;Zhang et al, 2017). Herbal medicine contains multiple compounds with different polarities.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the retrieval from the database and literature, the results of the compound analysis techniques (eg. LC-MS/MS analysis) may better reflect the true composition of herbal extracts (Liu et al, 2018a;Wang et al, 2019). Previous research has shown that Herba Lysimachiae (HL), the dried entire plant of Lysimachia paridiformis Franch.…”
Section: Introductionmentioning
confidence: 99%